Fauna of Oribatid mites (Acari, Oribatida) from the Movile Cave area (Dobrogea, Romania) - OTILIA IVAN; NICULAI ALEXANDRU VASILIU (Travaux de l'Institut de Speologie Emile Racovitza, 2010)
The paper discusses the results of the investigations performed on the oribatid fauna collected from the Movile Cave area. 35 species, belonging to 25 genera and 17 families have been identified; among them 2 genera and 6 species are new for the Romanian fauna. The taxonomic and zoogeographical spectrum of the fauna was analyzed, as well as the occurrence of the species depending on depth